2023
DOI: 10.1097/md.0000000000033870
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of severe COVID-19 complicated with cerebral infarction: Considerations on a case report

Abstract: Rationale: The standardization, individualization, and rationalization of intensive care and treatment for severe patients have improved. However, the combination of corona virus disease 2019 (COVID-19) and cerebral infarction presents new challenges beyond routine nursing care.Patient concerns and diagnoses: This paper examines the rehabilitation nursing of patients with both COVID-19 and cerebral infarction as an example. It is necessary to develop a nursing plan for COVID-19 patients and implement early reh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…When COVID-19 patients suffer from cerebral infarction meanwhile, it is essential to develop an individualized treatment plan for them. In addition to the conventional antibacterial treatment and the treatment of eliminating phlegm and relieving asthma for COVID-19 patients, anti-coagulation treatment should be actively applied, blood pressure and blood lipid should be measured, and the immunity of patients should be enhanced [ 8 ]. In conclusion, genetic susceptibility of critically ill COVID-19 infection is strongly linked to the increased risk of cerebral infarction, especially in the elderly and infants, and prevention and treatment of related patients is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When COVID-19 patients suffer from cerebral infarction meanwhile, it is essential to develop an individualized treatment plan for them. In addition to the conventional antibacterial treatment and the treatment of eliminating phlegm and relieving asthma for COVID-19 patients, anti-coagulation treatment should be actively applied, blood pressure and blood lipid should be measured, and the immunity of patients should be enhanced [ 8 ]. In conclusion, genetic susceptibility of critically ill COVID-19 infection is strongly linked to the increased risk of cerebral infarction, especially in the elderly and infants, and prevention and treatment of related patients is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The nervous system is the most complex part of the body, and when the disease of the nervous system encounters COVID-19, the diagnosis, treatment and prognosis of patients will face a severe test. For many neurosurgical diseases, the duration of treatment has been significantly reduced due to better maintenance of health services during the COVID-19 pandemic, and life care has been improved for critically ill patients and those requiring recovery [ 8 ], but the impact of COVID-19 on overall survival has varied. Some patients did not have a significant influence on their survival and prognosis due to the COVID-19 pandemic [ 9 ], but it has also been reported that COVID-19 infection is a risk factor for poor prognosis of some craniocerebral diseases [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%